What is the relation between the usage of GLP-1 analogs and obesity treatment? (Research, Society and Development, 2023)
Obesity is a global public health problem, which finds itself in a growing number of cases. This illness is associated with high morbimortality in the population and also various pathologies, such as diabetes mellitus type 2 and cardiovascular diseases. The main therapeutic intervention for this condition is lifestyle changes, contemplated by the practice of physical exercises, linked to hypocaloric diets. Nevertheless, plenty of patients don't obtain success in treating this infirmity, due to diligence and psychosocial factors intrinsic to this infirmity. In this scenario, GLP-1 analogs emerge as effective medicines in obesity treatment in patients who have no improvement with lifestyle changes isolated. In light of this, the article at stake aims to discuss the relationship between the usage of GLP-1 analogs and obesity treatment, highlighting its effects on weight loss and its limitations. It's, therefore, a literature integrative review, which was guided by parameters such as elaboration of a guiding question and keywords, inclusion and exclusion criteria, data gathering, and critical analysis of included surveys. To this end, surveys from the last 5 years that answered the leading and fit the inclusion and exclusion criteria question were utilized. The following survey, thus, emphasizes that GLP-1 analogs have effects on weight loss, glycemia, and cardiovascular risk.